Central and peripheral neural control of pancreatic exocrine secretion - Niebergall-Roth, Elke; Singer, Manfred V. (Journal of physiology and pharmacology, 2001)
Efferent vagal impulses act on the exocrine pancreas via pancreatic ganglia, where the impulses are modulated and modified, and terminate via postganglionic fibers at the acinar cells. Acinar muscarinic receptors of the subtype M1 play an important role for the mediation of the stimulatory vagal influences on pancreatic exocrine secretion. In dogs, a potentiative interaction exists between the two most important mediators of the pancreatic exocrine response to intraduodenal stimuli, efferent vagal impulses and CCK. In contrast to humans and rats, in which all action of CCK on pancreatic enzyme output is vagally mediated, CCK acts in dogs in part as a classical humoral factor independent of the cholinergic system. Although several peptides found in pancreatic nerve cell bodies or fibers can stimulate or inhibit pancreatic exocrine secretion, their physiological importance in the neural control of the exocrine pancreas needs to be further evaluated.